Kesiapsiagaan Mitigasi Bencana Gempa Bumi Pada Mahasiswa Asrama Universitas Syiah Kuala - Muhammad Apria Huda; Novia Zalmita (Universitas Syiah Kuala, Banda Aceh, 2026)
ABSTRAK Pemahaman kesiapsiagaan mitigasi bencana penting untuk dipahami bagi mahasiswa asrama Universitas Syiah Kuala. Tujuan penelitian ini adalah untuk menyelidiki kesiapsiagaan penghuni Asrama Mahasiswa Universitas Syiah Kuala terhadap bencana gempa bumi. Populasi penelitian terdiri dari 1.500 penghuni asrama, dengan 316 orang diambil sebagai sampel. Metode pengumpulan data menggunakan kuesioner, kemudian dianalisis secara deskriptif dengan rumus indeks kesiapsiagaan mitigasi bencana. Berdasarkan hasil penelitian disimpulkan bahwa tingkat kesiapsiagaan parameter pengetahuan dan sikap (Knowledge) pada kategori sangat siap (91%). Tingkat kesiapsiagaan parameter rencana tanggap darurat (Emergency Preparedness) pada kategori siap (79%). Tingkat kesiapsiagaan parameter sistem peringatan bencana (Warning System) pada kategori siap (78%). Tingkat kesiapsiagaan parameter mobilisasi sumber daya (Resource Mobilization Capacity) pada kategori sangat siap (80%). Secara keseluruhan keempat parameter berada pada kategori sangat siap (88%). Dengan ini diharapkan berbagai pihak yang berada pada lingkungan Asrama Mahasiswa Universitas Syiah Kuala dapat terus meningkatkan edukasi mengenai kesiapsiagaan mitigasi bencana gempa bumi. Kata Kunci: Kesiapsiagaan, Gempa Bumi, Penghuni Asrama ABSTRACT Understanding disaster mitigation preparedness is crucial for students residing in the dormitories of Syiah Kuala University. The aim of this study is to investigate the preparedness of dormitory residents at Syiah Kuala University towards earthquake disasters. The study population consists of 1,500 dormitory residents, with 316 individuals sampled. Data collection was conducted using questionnaires and analyzed descriptively using the disaster mitigation preparedness index formula. Based on the research findings, it was concluded that the preparedness level for the knowledge and attitude parameter (Knowledge) is categorized as very prepared (91%). The preparedness level for the emergency response plan parameter (Emergency Preparedness) is categorized as prepared (79%). The preparedness level for the disaster warning system parameter (Warning System) is categorized as prepared (78%). The preparedness level for the resource mobilization capacity parameter (Resource Mobilization Capacity) is categorized as very prepared (80%). Overall, all four parameters are classified as very prepared (88%). It is hoped that various parties within the Syiah Kuala University dormitory environment will continue to enhance education regarding earthquake disaster mitigation preparedness. Keywords: Preparedness, Earthquakes, Dormitory Residents